2020
DOI: 10.1007/s13369-020-04840-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics-Based Simulation on Chemical Flooding Produced Emulsion Formation and Stabilization: A Critical Review

Abstract: Oil-water emulsions are commonly encountered at various stages of petroleum production. For example, the alkaline-surfactant-polymer (ASP) flooding is extensively used to promote emulsion formation, and thus, enhance oil recovery (EOR). However, the chemicals (e.g. polymers and surfactants) involved in this process can also stabilize the produced emulsions to adversely affect the subsequent processes of oil field surface systems. Therefore, a deep understanding of oil-water emulsions formation and stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…To analyze the diffusion properties of wax–asphaltene molecules on the non-coated wall surface, the mean square displacement (MSD) is introduced here to reflect the deviation of the spatial position of a particle from its initial position during the MD simulation, and the MSD expression is as follows. where N is the number of diffusing molecules in the simulation system; r i ( t ) is the position of particle i at time t ; and r 0 ( t ) is the position of particle i at the initial time. A larger slope of the MSD curve indicates that the target molecule is more capable of migration and movement. , Furthermore, the MSD curve can also be converted into the diffusion coefficient D through the Stocks–Einstein formula to realize the quantitative characterization of the target molecular motion properties …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To analyze the diffusion properties of wax–asphaltene molecules on the non-coated wall surface, the mean square displacement (MSD) is introduced here to reflect the deviation of the spatial position of a particle from its initial position during the MD simulation, and the MSD expression is as follows. where N is the number of diffusing molecules in the simulation system; r i ( t ) is the position of particle i at time t ; and r 0 ( t ) is the position of particle i at the initial time. A larger slope of the MSD curve indicates that the target molecule is more capable of migration and movement. , Furthermore, the MSD curve can also be converted into the diffusion coefficient D through the Stocks–Einstein formula to realize the quantitative characterization of the target molecular motion properties …”
Section: Resultsmentioning
confidence: 99%
“…The interaction energy is an important parameter to determine the strength of the interaction between two contacting materials, , and it reflects the interaction strength between the heavy component molecules and coated wall surface in this paper. The higher the absolute value of interaction energy, the stronger the bond of heavy component molecules with the coated wall surface, which also means the stronger the adsorption of heavy component molecules on the coated wall surface. where E total is the total energy of the system, kJ/mol; E Interaction is the interaction energy between heavy component molecules and non-coated and coated wall surface, kJ/mol; E non‑coated is the total energy of the non-coated wall system, kJ/mol; E coated is the total energy of the coated wall system, kJ/mol; E wax is the total energy of wax molecules, kJ/mol; E asp is the total energy of asphaltene molecules, kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the challenges on ASP floodingproduced water, scholars have performed a series of basic studies on the emulsion stability mechanism. Wang et al 14 investigated the effects of oil-displacing agent composition on the oil/water emulsion stability by interfacial tension (IFT) meters, microscopes, and zeta potential analyzers. Both alkali and surfactants play dual roles in the ASP system.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with experimental analysis methods, molecular dynamics (MD) simulation has unique advantages in microstructure characterization; so in recent years, it has become a trend to explore the aggregation structure of asphaltene and resin molecules from the microscale by molecular simulation [15]. Many studies have shown that the interaction between polar molecules is mainly through the π − π stacking of aromatic rings.…”
Section: Introductionmentioning
confidence: 99%